Analysis of Improvement in Pharmacy Services Based on The IPA Model At Pharmacy X Ijen Malang - Dian Nurmawati; Arifani Siswidiasari; Rahmaweni (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Patient satisfaction is pleasure after receiving services that meet or exceed expectations. Patient satisfaction surveys should be conducted at Apotek at least once every 6 months, including Apotek Kimia Farma 36 Ijen. Pharmaceutical services are direct and responsible services to patients related to pharmacy to achieve tangible results and improve the patient's quality of life. This research aimed to measure patient satisfaction with pharmaceutical services at Apotek Kimia Farma 36 Ijen. The method used is descriptive research with a quantitative approach through a questionnaire instrument using the SERVQUAL (Service Quality) model with incidental sampling techniques. The statement on the questionnaire that had the highest satisfaction was the pharmacist who did not look at the patient's social status and the friendliness of the pharmacy staff. In contrast, the lowest satisfaction was the statement of quality drug supply. The research results showed that patients were satisfied with pharmaceutical services at Kimia Farma 36 Ijen Pharmacy by obtaining a satisfaction level of 68.39%.